2012
DOI: 10.5005/jp-journals-10024-1182
|View full text |Cite
|
Sign up to set email alerts
|

Maxillomandibular Plane Angle Bisector (MM) Adjunctive to Occlusal Plane to evaluate Anteroposterior Measurement of Dental Base

Abstract: Aim This study was undertaken to analyze the clinical usefulness of the maxillomandibular bisector, its reproducibility, its validity and its relationship to the functional occlusal plane, the bisecting occlusal plane and the nature of its cant. Materials and methods Thirty pretreatment lateral cephalograms, each of adolescents (above 18 years of age) and children (10- 12 years), seeking orthodontic treatment were randomly selected and the Wits technique of anteroposterior measurement was used to compare A-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This study is in concordance to our study. Scott JH, 11 Ganiger RC (2012) 1 found that AB-MM is more reliable because the MM bisector is highest stable plane with the relation of cranial base. It is recommended that the orthodontist can use AB-MM parameter for judging the anterio-posterior skeletal discrepancy with better accuracy and validity than its contemporary parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is in concordance to our study. Scott JH, 11 Ganiger RC (2012) 1 found that AB-MM is more reliable because the MM bisector is highest stable plane with the relation of cranial base. It is recommended that the orthodontist can use AB-MM parameter for judging the anterio-posterior skeletal discrepancy with better accuracy and validity than its contemporary parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of an important part of orthodontic treatment and the greatest thrust in this direction evolved with advent of radiographic cephalometry by Broadbent in 1931. 1,2 Although many cephalometric analysis have been devised to determine the degree of anteroposterior skeletal discrepancies, effective treatment planning and assessment must be based on accurate measurement using stable and reproducible reference planes. Despite the popularity of the ANB angle, 1 Jacobso 3 noted that this measurement does not always accurately relate the true anteroposterior relationship of the jaws.…”
Section: Introductionmentioning
confidence: 99%